Small island seagrass ecosystem management based on ecosystem approach fisheries management principles - Mutmainnah Mutmainnah; Yuliana Yuliana; Khamsiah Achmad; Martini Djamhur; Sapta Riani Putri; Edy Miswar; Edwarsyah Edwarsyah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Healthy seagrass beds have high ecological value, characterized by high diversity and even distribution in the water. However, currently, the health condition of seagrass beds is threatened both naturally and by human activities. For example, the loss of seagrass meadows due to human activities in coastal areas, including on Maitara Island, North Maluku Province, Indonesia. The objective of this research is to identify the community structure of seagrass, and the proper management options to minimize negative impacts on damage to the seagrass meadow ecosystem and sustain seagrass resources. The study was conducted in the South Maitara and the North Maitara, during the dry season from September to October 2020 using vertical transect methods. The result shows that the average index of diversity, evenness, and dominance on Maitara Island of 1.0970, 0.6470, and 0.5892, respectively. The beaches of South Maitara and North Maitara have poor diversity, a good category for evenness, and a stable community. Enhalus acoroides has the highest density of 294 ind/m2, followed by Thalassia hemprichii around 287 ind/m2. Based on the ecosystem aproach fisheries management (EAFM) analysis, to effectively manage seagrass ecosystems in Maitara Island, a social development strategy is needed through community awareness, counseling, and capacity building in the management and utilization of seagrass ecosystems in Maitara Island to effectively manage the seagrass ecosystem in Maitara Island, a social development strategy is needed through public awareness, counseling, and capacity building in the management and utilization of the seagrass ecosystem in Maitara Island.Keywords:Seagrasscommunity structurediversitydensityevennessMaitara Island